Research and Design of High Altitude Wind Power Station Operation and Maintenance Auxiliary System - Hang HE; Shaoyong WANG; Jiakang ZHOU; Yuan YANG; Wenjun ZHANG; Kan LIN (南方能源建设)
[Objective] At present, domestic and international research on high-altitude wind power generation technology has been carried out, mainly in the fields of operation control, mechanism analysis and system design, but no research results have been found in the field of high-altitude wind power station operation and maintenance. [Method] This paper proposed a design scheme of intelligent operation and maintenance assistance system for high-altitude wind power stations, which provided ideas for the future popularization and application of intelligent operation and maintenance technology in high-altitude wind power stations and the promotion of digital operation and maintenance construction. Based on the investigation of China's first demonstrative high-altitude wind power station with an umbrella-ladder combination system, the pain points of operation and maintenance at the present stage were analyzed, and a set of intelligent operation and maintenance assistance system was designed to solve the problems such as scattered monitoring and background in the station, various operating data forms, unsystematic equipment records and inconvenient tracing of fault maintenance history. [Result] Based on microservices, an intelligent operation and maintenance visualization platform for high-altitude wind power station is developed to realize centralized monitoring of power generation system equipment status, standardization of equipment records and maintenance ticket process, monitoring of operating environment safety, active identification of dangerous events and output alarm. [Conclusion] High-altitude wind power station is an emerging concept in energy sector. The design of its intelligent operation and maintenance platform should first focus on improving the centralized visualization degree of power station operation data, promoting the digital management mode of equipment and ensuring the safety of power station operation environment, so as to match the operation and maintenance requirements of power station in the initial stage. With the advance in the core control technology, equipment selection and manufacturing technology of high-altitude wind power generation system in the future, the intelligent operation and maintenance technology of high-altitude wind power station can be adapted to the progress, and further promote the rise of high-altitude wind power station.